Consumption of fruits and vegetables among college students living in dormitory in Shahid Beheshti University of Medical Sciences - Ramezankhani, Ali; Gharlipour, Zabihollah; Motalebi, Masuod; Babaei Heydarabadi, Akbar; Bazhan, Marjan; Imanzad, Masoumeh; Vafaee, Reza; Tavassoli, Elahe (Archives of Advances in Biosciences, 2013)
Obesity is rising rapidly in Iran. Nutrition is an important issue of obesity; Fruits and vegetables are among the best food sources of antioxidant vitamins, soluble fibers, phytochemicals, and other nutrient constituents. Further, some of these foods have been shown to be protective related to reduction of chronic disease risk. In this study, consumption of fruits & vegetables and body mass index (BMI) among College Students Living in dormitory at Shahid Beheshti University of medical sciences were evaluated. In this descriptive analytic survey, 658 college students whose have being lived in dormitory at Shahid Beheshti University of medical sciences were selected by clustering sampling method. Data collected using a food frequency questionnaire and analyzed by SPSS16 software. Mean age of participants was 21.82 for females and 22.76 years for males. Frequency of fruits consumption was 2.6± 0.9 per day in female and 2.3±0.7 in male, while frequency of vegetables consumption was 3.2±1.00 in female and 2.9± 0.9 per day in male students. In general, consumption of fruits (p=0.003) and vegetables (p<0.001) were significantly more in female than males students. BMI in students was normal. Results indicated that students hadn’t optimal practice towards fruits and vegetables consumption. Thus, it is essential that authorities pay more attention to this specific problem in training the students, in order to maintain the optimal nutritional status.